A Hacker in Every History Department: An Intelligent Radical’s Guide to the Digital Humanities - Potter, Claire Bond (Radical Teacher, 2014)
Rather than making the next generation of history Ph.D.'s redundant or contingent laborers, digital technologies and the Internet have the potential to revive full time teaching. Although Digital Humanities is growing rapidly as a field, few history departments have tapped into the power of its pedagogy to teach critical thinking and research skills. Focused on making, rather than banking, knowledge, DH emphasizes flexibility and originality. Furthermore, by giving historians the technical and design skills to work outside the academy, it not only produces a new source of employment but would force universities to compete for historians just as they do for lawyers, economists and scientists.